Bedah Kasus- Salah Satu Teknik Pembelajaran Student Centered Learning untuk Mengasah Kompetensi Manajemen - Rahmini Hadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Case analysis method are a type of learning by doing, that widely accepted as more superior to shape managerial skills compared with regular teaching method. This management skill is enhanced with quality case as much as possible. Several usefulness of case analysis is trying to identifying management issues, evaluating alternative solution, and formulates workable action planning. Also enhance student business-judgment, and get in-depth exposure on many industrial and company environment.Â